HEDGING, FUTURE CONTRACT DENGAN OPTION CONTRACT UNTUK MEMINIMALISASI RESIKO FLUKTUASI KURS VALAS - Zeinora Zeinora (Sosio e-Kons, 2016)
Company, which conducts international transactions such as export-import, generally will be faced by the changing of exchange rate risk or foreign exchange exposure. The changing of the changes exchange risk has potential impact to level of profitability, net cash flow and the company’s market value. This risk will be cause the Multi National Corporation (MNC) faces the possibilities problems of the transaction losses due to exchange fluctuation. To solve these type of problems, the company can use Hedging. Hedging is a tool of risk management techniques which use derivatives as alternative. In this study, researcher choose 2 types of derivative hedging instrument which are option contract and future contract hedging. This study aims to compare both derivative hedging instrument based on literature review. Keywords : Hedging, future contract, and option contract.